A novel approach for assessing the ports’ environmental impacts in real time – The IoT based port environmental index - Matija Široka (Elsevier, 2021)
In recent years, exchange of goods around the world has mostly been done by the sea, which increased the pollution coming from the port areas. Activities connected with shipping and handling of goods in ports may harm both human health and the environment. These activities include different (mostly diesel-fueled) machinery used in ports, resulting in air emissions including GHG, NOX, SOX, PM, etc. Besides air pollution, port activities affect noise, light, and odor emission, waste accumulation and water pollution. Existing methodologies for estimating environmental impacts of port activities are mostly qualitative and include self-assessment methods which can often lead to biased results. Because of that, there is a need for a quantitative, industry-validated, and cohesive method that would give more accurate results. In this article, the Port Environmental Index (PEI) which has all the attributes described above will be presented. The PEI mission is to integrate all of the main environmental aspects of port such as air emission, waste production, water pollution, noise, light, and odor pollution into one metric that can then be used to assess the port performance and make comparison between ports. The PEI is made as a quantitative composite index based on aggregations of individual indicators for significant aspects of port operations. It includes different indices according to the source of the emission; the Ship Environmental Index (SEI), the Terminal Environmental Index (TEI), and the Port Authority Environmental Index (PAEI). While designing the PEI, correctly choosing the environmental impacts is paramount to properly identify port activities and associated environmental aspects. After their identification, for each significant aspect, a set of representative environmental key performance indicators (eKPIs) is identified. Afterwards, a series of mathematical operations are to be applied: normalization, weighting and aggregation. In this short communication, those methods are outlined yet not definitively chosen. The main idea behind the PEI is to use quantitative, data-based information collected automatically leveraging Internet of Things (IoT) techniques making it possible to assess the environmental impacts of port operations in real-time. The advantages of having such metric in the environmental management plan of a port are numerous. Amongst the most remarkable, it allows inter-port comparison and it can be used for decision making to estimate the impacts using one single metric rather than having many disperse values. Moreover, it can be used by ports for estimating their environmental performance and progress. Since it is based on information collected using IoT technologies provided in real-time, ports can make immediate corrections in their activities.